1999
DOI: 10.1046/j.1365-2044.1999.00958.x
|View full text |Cite
|
Sign up to set email alerts
|

Hemispheric‐synchronisation during anaesthesia: a double‐blind randomised trial using audiotapes for intra‐operative nociception control

Abstract: SummaryThe possible antinociceptive effect of hemispheric-synchronised sounds, classical music and blank tape were investigated in patients undergoing surgery under general anaesthesia. The study was performed on 76 patients, ASA 1 or 2, aged 18-75 years using a double-blind randomised design. Each of the three tapes was allocated to the patients according to a computer-generated random number table. General anaesthesia was standardised and consisted of propofol, nitrous oxide 66%/ oxygen 33%, isoflurane and f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
0
3

Year Published

2006
2006
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 23 publications
1
35
0
3
Order By: Relevance
“…[1][2][3] Such binaural beats have been described to be brainstem responses that originate in the superior olivary nucleus of each cerebral hemisphere and are thought to cause hemispheric synchronization. 1,2 This modality is promoted as a treatment for stress, anxiety, pain control, and other conditions (http://www.monroeinstitue.org).…”
mentioning
confidence: 99%
“…[1][2][3] Such binaural beats have been described to be brainstem responses that originate in the superior olivary nucleus of each cerebral hemisphere and are thought to cause hemispheric synchronization. 1,2 This modality is promoted as a treatment for stress, anxiety, pain control, and other conditions (http://www.monroeinstitue.org).…”
mentioning
confidence: 99%
“…31 Another major field where music-listening interventions are applied is to support patients' recovery after surgery and to ease postoperative pain. Within this setting, the patient listens to music before the operation (preoperative [32][33][34], during the operation (intraoperative 32,[35][36][37][38][39][40], or after the operation (postoperative 33,35,38,39,. The type of operations and patients where music listening has been applied include patients undergoing vascular and thoracic surgery 42 ; patients who underwent a total knee arthroplasty 40,41 or hip or knee surgery 62 ; elderly orthopedic patients 53 ; patients undergoing coronary artery bypass 35 ; children undergoing oral surgeries 32 ; patients undergoing abdominal surgery 43,45,48 ; and women undergoing gynecologic surgery, 44,49,52 intestinal surgery, 46 thyroid, parathyroid, or breast surgery.…”
Section: Music Listening To Reduce Painmentioning
confidence: 99%
“…51 Furthermore, music listening has been applied to patients who have undergone open heart surgery, 55,60 cardiac surgery, 56 nasal surgery, 59 or coronary artery bypass graft (CABG) surgery. 61 Besides those distinct surgical procedures, studies on the pre-, intra-, or postoperative effects of listening to music include surgery in general, 33,34,36,47,50,57 urologic procedures, 37 hysterectomy patients, 38,58 or day case surgery for inguinal hernia repair or varicose vein surgery, 39,54,63 where general or spinal anesthesia is applied. Several studies also report that listening to music reduces labor pain.…”
Section: Music Listening To Reduce Painmentioning
confidence: 99%
“…There have also been several studies in anaesthesiology that have investigated the ability of music to reduce patients' anxiety and pain, both during general and spinal anaesthesia as well as during conscious sedation 22,30,33,35 . An intra-operative, randomised clinical trial of 50 patients undergoing surgery with spinal anaesthesia found that the group of patients who received intra-operative music via headphones had significant reductions in midazolam requirements (p < 0.05) throughout the entire peri-operative period in comparison to patients who received no music 30 .…”
Section: Music Therapy In Anaesthesiologymentioning
confidence: 99%